Air Carrier’s Liability for Damages According to the New Montreal Convention - Kaštela, Slobodan; Miljak, Zvonko; Božičević, Josip (Promet - Traffic&Transportation, 2012)
The liability of air carriers in international air traffic is stillregulated by the Warsaw Convention from 1929and its amendments.In 1999the Montreal Convention was accepted, whichcompletely substitutes the rules contained in the Warsaw Conventionincluding all its later amendments, and the most importantmodifications have been made regarding the air can·iers’liabilities in case of passenger injury or death on intemationaI flights.